Clinical results of resection arthrodesis by triangular external fixation for posttraumatic arthrosis of the ankle joint in 89 cases - Kiene, J (BioMed Central, 2009)
The methods for ankle arthrodesis differ significantly, probably a sign that no method is clearly superior to others. In the last ten years there is a clear favour toward internal fixation. We retrospectively evaluate the technique and evaluate the clinical long term results of external fixation in a triangular frame. PATIENTS AND METHODS: From 1994 to 2001 a consecutive series of 95 patients with end stage arthritis of the ankle joint were treated. Retrospectively the case notes were evaluated regarding trauma history, medical complaints, further injuries and illnesses, walking and pain status and occupational issues and the clinical examination before arthrodesis. Mean age at the index procedure was 45.4 years (18-82), 67 patients were male (70.5%). Via a bilateral approach the malleoli and the joint surfaces were resected. An AO fixator was applied with two Steinmann-nails inserted with approximately 8 cm distance in the distal tibia, one in the neck of the talus and one in the dorsal calcaneus. The fixator was removed after approximately 12 weeks. Follow up examination at mean 4.4 years included a standardised questionnaire and a clinical examination including the criteria of the AOFAS-Score and radiographs. Results: Due to different complications, 8 (8.9%) further surgical procedures were necessary including 1 below knee amputation. In 4 patients a non-union of the ankle arthrodesis developed (4.5%). The mean AOFAS score improved from 20.8 to 69.3 points. CONCLUSION: Non-union rates and clinical results of arthrodesis by triangular external fixation of the ankle joint do not differ to internal fixation methods. The complication rate and the reduced patient comfort reserve this method mainly for infected arthritis and complicated soft tissue situations.